2015
DOI: 10.2146/ajhp140257
|View full text |Cite
|
Sign up to set email alerts
|

Applying lean principles to continuous renal replacement therapy processes

Abstract: The use of lean principles to identify medication waste in the CRRT workflow and implementation of an intervention to shift the workload from intensive care unit nurses to pharmacy technicians led to reduced CRRT solution waste, improved efficiency of CRRT workflow, and increased satisfaction among staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…This latter impact will vary by the characteristics of a given medical center, including personnel costs and volume of CRRT care. In our medical center, we have also observed significant medical waste of CRRT solutions which we believe is in part related to a limited shelf life for use (12 hours) after manipulation for electrolyte additives . Another difficult to quantify consideration is the potential cost from adverse events should they occur.…”
Section: Special Considerations For Phosphate‐containing Crrt Solutionsmentioning
confidence: 99%
“…This latter impact will vary by the characteristics of a given medical center, including personnel costs and volume of CRRT care. In our medical center, we have also observed significant medical waste of CRRT solutions which we believe is in part related to a limited shelf life for use (12 hours) after manipulation for electrolyte additives . Another difficult to quantify consideration is the potential cost from adverse events should they occur.…”
Section: Special Considerations For Phosphate‐containing Crrt Solutionsmentioning
confidence: 99%
“…While mortality is an obvious metric that should be tracked, it may be difficult to ascribe survival from only one procedure in these critically ill complex patients. Given the known high mortality in this population, additional metrics examining surrogate outcomes or areas such as process of care are needed [20]. One of the few evidence-based metrics available for CRRT is the delivered effluent dose, for which it has been established target of 20–25 mL/kg/hr in adults [21–23].…”
Section: Nephrologist As Leaders For Acute Rrt Programsmentioning
confidence: 99%
“…Clinical exploration has begun to address the causes associated with unplanned interruptions so as to reduce its rate of occurrence. For example, Benfield et al ( 11 ) applied lean thinking to the workflow of CRRT and confirmed that it could improve the quality of care. Sanchez-Izquierdo-Riera et al ( 12 ) applied failure modes and effects analysis to improve the safety of CRRT, and the observation group used the filter for a longer period of time than the control group.…”
Section: Discussionmentioning
confidence: 99%